2018
DOI: 10.1080/2162402x.2017.1414119
|View full text |Cite
|
Sign up to set email alerts
|

The immunocytokine L19-IL2: An interplay between radiotherapy and long-lasting systemic anti-tumour immune responses

Abstract: Recently, we have shown that the administration of the tumour-targeted antibody-based immunocytokine L19-IL2 after radiotherapy (RT) resulted in synergistic anti-tumour effect. Here we show that RT and L19-IL2 can activate a curative abscopal effect, with a long-lasting immunological memory. Ionizing radiation (single dose of 15Gy, 5 × 2Gy or 5 × 5Gy) was delivered to primary C51 colon tumour-bearing immunocompetent mice in combination with L19-IL2 and response of secondary non-irradiated C51 or CT26 colon tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 69 publications
(48 reference statements)
3
35
0
Order By: Relevance
“…39 Rekers et al showed that colon cancer tumors in immunecompetent mice treated with radiation in combination with the L19-IL-2 ICK resulted in long-lasting anti-tumor responses, including an abscopal effect. 40 Also in that study cured mice showed immune memory against tumor rechallenge. However, in our breast cancer model, immune memory responses were observed only in mice treated with fractionated SRT and ICK, suggesting that single high dose SRT has an immunosuppressive effect.…”
Section: Discussionmentioning
confidence: 85%
“…39 Rekers et al showed that colon cancer tumors in immunecompetent mice treated with radiation in combination with the L19-IL-2 ICK resulted in long-lasting anti-tumor responses, including an abscopal effect. 40 Also in that study cured mice showed immune memory against tumor rechallenge. However, in our breast cancer model, immune memory responses were observed only in mice treated with fractionated SRT and ICK, suggesting that single high dose SRT has an immunosuppressive effect.…”
Section: Discussionmentioning
confidence: 85%
“…As such, this drug has the potential to boost selective anti-tumoural immune responses in patients with NSCLC. We have demonstrated in preclinical studies that L19-IL2, especially in combination with radiotherapy, results in improved disease control in lung and colorectal carcinoma models [21,23]. Therapeutic responses were dependent on the irradiation dose, the target expression levels and are causally related to the presence of CD8 + cytotoxic T cells [21].…”
Section: Rationalementioning
confidence: 99%
“…Best responses were found when administrating L19-IL2 after radiotherapy [40,41]. Additionally, we have shown that this combination leads to improved local tumour control as well as tumour regression outside of the radiotherapy field and induces an immune-mediated memory effect preventing tumour-relapse after reinjection of tumour cells [23]. Furthermore, in pre-clinical Lewis Lung Carcinoma (LLC) models, we have observed that the synergy of radiotherapy with L19-IL2 is superior to the combination of radiotherapy with ICI.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“… 30 Administration of the immunocytokine L19-IL2 in combination with radiation therapy (a single dose of 15 Gy) induced the abscopal effect in 20% of the immunocompetent mice with colon tumours. 31 Administration of the granulocyte-macrophage colony-stimulating factor also promoted the occurrence of the abscopal effect in patients with metastatic cancer. 32 The toll-like receptor 7 (TLR7) agonist imiquimod promoted the radiation therapy-elicited in situ vaccination, thereby enhancing the incidence of the abscopal effect.…”
Section: The Factors Promoting the Occurrence Of The Abscopal Effectmentioning
confidence: 99%